26 CORONARY MICROVASCULAR DYSFUNCTION: IT COULD BE (ALSO) A MAN'S WORLD!. (15th December 2022) - Persampieri, Simone; Baluci, Martino; Schaffer, Alon; De Martino, Leonardo; De Pace, Doranna; Lupi, Alessandro
Abstract: Introduction: Coronary microvascular dysfunction (CMD) is one of the possible manifestation of ischaemic heart disease with signs and symptoms of myocardial ischaemia, but no obstructive coronary artery disease (CAD). CMD is defined by an impaired coronary flow reserve owing to functional and/or structural abnormalities of the microcirculation and it is associated with adverse cardiovascular prognosis. Women are known to be more likely than men to have angina in the absence of obstructive CAD and CMD has been proposed as one of the major reasons for this presentation. However, also in men, CMD should be recognized, in order to give the best treatment to relieve symptoms and improve patient prognosis. Index of microvascular resistance (IMR) and coronary flow reserve (CFR) are needed to diagnose CMD and are now easily obtained with pressure wires measurement. Methods: Since the adoption in our Cath Lab of the PressureWire™ X Guidewire with the Coroventis CoroFlow Cardiovascular System (Abbott) we started to study IMR and CFR in patients with no obstructive CAD and typical angina. No acute coronary syndromes have been studied in our Cath Lab so far. In this brief study we report a descriptive analysis of the first patients studied and of the first period of follow-up, focusing on men. Results: From January 2022 (date when we received the new software) to April 2022 we studied 24 patients and 8 (33%) were men. Among men, mean age was 58±5 yo and two have been already treated with PCI during the previous 6 months. Mean ejection fraction was 57±2% and mean GFR was 76±20 ml/min/mq. 7 out of 8 patients were affected by dyslipidemia, 5 were smoker, 50% were affected by arterial hypertension and only 1 by diabetes. Mean RFR and FFR in left anterior descending artery were 0.92±0.02 and 0.92±0.03, respectively. In 6/8 (75%) patients IMR derived was >25 and, among them 4 (66%) had CFR<2. After coronary study we tried to optimize medical therapy in all these patients, adding or changing to Zofenopril previous ACE inhibitor therapy, adding or titrating Ranolazine and adding or titrating negative chronotropic therapy (beta blockers or calcium channel blockers). After therapy optimization none of the patients had resumption of symptoms (follow-up from 3 to 7 months). Conclusions: Even if historically considered a women's disease, we should remember that CMD also affects men. New widespread technologies should be used systematically to rule out CMD and to define patients' symptoms mechanisms. This would lead to targeted therapy that could improve patient's lives.